2021
DOI: 10.1177/00219983211002237
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of spent coffee ground derived biochar reinforced epoxy composites

Abstract: Semi-crystalline carbon biochar is derived from spent coffee grounds (SCG) by a controlled pyrolysis process at high temperature/pressure conditions. Obtained biochar is characterized using XRD, SEM, and TEM techniques. Biochar particles are in the micrometer range with nanostructured morphologies. The SCG biochar thus produced is used as reinforcement in epoxy resin to 3 D print samples using the direct-write (DW) method with 1 and 3 wt. % loadings. Rheology results show that the addition of biochar makes res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Biochar derived from SCG (1 and 3 wt.%) was also used to obtain thermoset-based composites for 3D printing [ 155 ]. Their particles presented a nanostructured morphology.…”
Section: Scg Polymer Compositesmentioning
confidence: 99%
“…Biochar derived from SCG (1 and 3 wt.%) was also used to obtain thermoset-based composites for 3D printing [ 155 ]. Their particles presented a nanostructured morphology.…”
Section: Scg Polymer Compositesmentioning
confidence: 99%
“…It was revealed that biochar with the highest porous morphology was the most effective in its reinforcing ability, thus improving the overall thermal and mechanical properties of the system . High-pressure/temperature pyrolysis reactions can be utilized to synthesize carbon with better inherent properties, thus allowing for lower loading wt % . Idrees et al reinforced recycled poly­(ethylene terephthalate) with packaging waste-derived biochar at loading as low as 0–5 wt % .…”
Section: Introductionmentioning
confidence: 99%
“… 19 High-pressure/temperature pyrolysis reactions can be utilized to synthesize carbon with better inherent properties, thus allowing for lower loading wt %. 20 Idrees et al reinforced recycled poly(ethylene terephthalate) with packaging waste-derived biochar at loading as low as 0–5 wt %. 21 The biochar can be further reduced in its size to make effective use of surface through postprocessing methods like activation, 22 , 23 ultrasonication, 24 , 25 and ball milling.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted on mixtures with finer grain sizes, classified by the authors as nanocomposites, indicate a beneficial effect of the use of biochar as an effective reinforcement [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%